Telomeres and disease: Enter TERRA - Maicher, André; Kastner, Lisa; Luke, Brian (RNA biology, 2012)
Telomere function is tightly regulated in order to maintain chromosomal stability. When telomeres become dysfunctional, the replicative capacity of cells diminishes and cellular senescence ensues. This can lead to impaired tissue replenishment and eventually degenerative disorders, referred to as telomere syndromes. Cancer can also develop as a result of the genomic instability associated with telomere dysfunction. TERRA (TElomeric Repeat containing RNA) is a long non-coding transcript that stems from sub-telomeric regions and continues into the telomeric tract and is therefore a hybrid of both sub-telomeric and telomeric sequence. In general, increased TERRA transcription is associated with telomere shortening and compromised telomere function. Here we will briefly outline the general principles behind telomere dysfunction-associated diseases. Furthermore, we will discuss the few known links that exist between telomere transcription (TERRA) and disease. Finally, we will speculate on how the understanding, and eventual manipulation, of TERRA transcription could potentially be used in terms of therapeutic strategies.